LAND RENT VALUE OF BLOOD SHELL PONDS (Anadara granosa) IN BANGKO DISTRICT ROKAN HILIR REGENCY RIAU PROVINCE - Delwita, Delwita; Warningsih, Trisla; Yulinda, Eni (Asian Journal of Aquatic Sciences, 2025)
The land rent value is one of the critical indicators in determining the profitability of blood cockle (Anadara granosa) cultivation and the efficiency of pond land utilization. This study aims to calculate the land rent value of blood cockle ponds and analyze the factors influencing land rent value in Bangko District, Rokan Hilir Regency, Riau Province. This study used a survey method with a census respondent selection technique involving 43 blood cockle farmers. Data were collected through interviews, observations, questionnaires, and literature studies. Data was analyzed using the rental value calculation method and multiple linear regression analysis. The results showed that the average land rent value of blood cockle ponds in Bangko District was IDR 49.777,968/ha, and the main factors that affect the rent value of blood mussel pond land are pond productivity and the distance of the pond location to the market center. This study concludes that the higher the productivity, the higher the land rent value, while the further the distance, the lower the land rent value